The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00181-016-1105-5
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian wage curve: new evidence from the National Household Survey

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In general, elasticities were lower or even became negative, a sign that the wage curve seemed to better express this specific period. This regression covered the same period studied by Baltagi et al (2017). Even though their results seemed to better confirm the expected shape of the wage curve, the main conclusions were very similar to the ones found here.…”
Section: The Rural-urban Dichotomy and The Wage Curvesupporting
confidence: 81%
See 1 more Smart Citation
“…In general, elasticities were lower or even became negative, a sign that the wage curve seemed to better express this specific period. This regression covered the same period studied by Baltagi et al (2017). Even though their results seemed to better confirm the expected shape of the wage curve, the main conclusions were very similar to the ones found here.…”
Section: The Rural-urban Dichotomy and The Wage Curvesupporting
confidence: 81%
“…Santolin and Antigo (2009) found that the wage curve seems to be non-dynamic in six metropolitan regions (PNAD data, 1997(PNAD data, -2005, but there is a higher wage flexibility for the whole group of workers (À0.15) than for formal workers (À0.05). More recently, Baltagi et al (2017) controlled for individual observed heterogeneity and state-level fixed effects, with the lagged unemployment rate as an instrument for current unemployment rate (PNAD, 2002(PNAD, -2009. They found that only for the informal sector is the unemployment elasticity significant (À0.251), and compared workers in the formal and informal sectors with similar probabilities of being formal, finding unemployment elasticities of À0.129 and À0.305, respectively.…”
mentioning
confidence: 99%
“…For the selection equation (the probability of working), the following variables were considered as potential control covariates: (1) education, (2) age, (3) gender, (4) a dummy variable equal to one for formal businesses, (5) a dummy variable equal to one if the person is indigenous, (6) the number of family members and (7) a dummy variable equal to one if the person is a household head. These variables were selected based on data availability and also following previous studies such as Baltagi et al (2017), who estimated the wage curve for Brazil and considered as control covariates the age of the individual, gender, race, education, the individual's years of tenure at a firm and formality of employment, among other variables available for Brazil. In Bolivia, the level of education and experience have a direct effect on the salary and on the probability of working; also, it is expected that differences in salary may exist for different age categories and between males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reviewer's suggestion, we updated the estimation with data from the more recent survey and, thus, this section presents results based on data from the 2017 household survey of Bolivia. In the results for 2006, the estimate of the wage curve elasticity for Bolivia was equal to 7%.3 A similar variable was included byBaltagi et al (2017) as a control covariate, household type, where the response categories were couples without children, couples with children, single mother with children, and…”
mentioning
confidence: 99%
“…But the wage variable is net of taxes and the estimates control for firm size. South Africa, 2000Africa, -2004 Close to zero in the short run and approximately -0.1 in the long run Baltagi et al (2017) Brazil, 2002 Aggregate = -0.107…”
Section: Parameter/variable Value In Base Casementioning
confidence: 99%